[PP.30.03] RELATIONSHIP BETWEEN URINE SODIUM/POTASSIUM EXCRETION AND CENTRAL AORTIC SYSTOLIC BLOOD PRESSURE IN KOREAN PATIENTS WITH HYPERTENSION. (September 2016) - Rhee, M.; Kim, J.H.; Shin, S.J.; Nah, D.Y.; Sung, K.C.; Cho, E.J.; Hong, K.S.; Jo, S.H.; Kim, K.I.; Lee, S.H.
Abstract : Objective: Although several studies showed the association of urinary salt excretion with central hemodynamics, the relationship between 24-hour urine sodium (24HUNa) and potassium (24HUK), and aortic blood pressure (BP) is uncertain in Asian. Design and method: From 707 randomly recruited participants, the relationship between 24HUNa and 24HUK, and casual BP, 24-hour ambulatory BP, and aortic BP were analyzed in 524 participants with valid 24-hour urine collection, 24-hour ambulatory BP and central BP measurement (age 48.1 ± 9.8 years, 193 men). Hypertension was defined by 24-hour ambulatory BP > = 130/80 mmHg, or current treatment of hypertension (n = 219). Results: Participants with hypertension and high 24HUNa (mean 214.7 ± 51.4 mmol/day, range 155.0–432.0) showed higher 24-hour systolic (p = 0.021) and diastolic BP (p = 0.036) and aortic systolic BP (AoSBP, p = 0.032) than participants with hypertension and low 24-HUNa (mean 118.4 ± 25.9 mmol/day, range 45.6–154.8) with adjustment for confounders. Participants with hypertension and high 24HUNa/24HUK ratio (mean 4.08 ± 1.00, range 3.00–7.95) had higher AoSBP than participants with hypertension and low 24HUNa/24HUK ratio (mean 2.17 ± 0.56, range 0.53–3.00) with adjustment for confounders (p = 0.038). Participants with hypertension showed a significant linear relationship between AoSBP and 24HUNa/24HUK ratio in multiple regression analysis, which was independent to 24HUNa (p = 0.047). In participants without hypertension, 24HUNa and 24HUNa/24HUK ratio were not associated with casual BP, 24-hour ambulatory BP and AoSBP. Conclusions: In Korean patients with hypertension, 24HUNa/24HUK ratio is independently related to AoSBP.